APPLICATION OF SOMATIC AUDITORY VISUALIZATION INTELLECTUALLY LEARNING STYLE TO IMPROVE THE UNDERSTANDING OF THE CONCEPT OF STRUGGLE TO MAINTAIN INDEPENDENCE - Pramuharti, Marlita; Hartono, Hartono; Kuswadi, Kuswadi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The purpose of this research is to improve the understanding of the concept of struggle to maintain independence with the implementation of Somatic Auditory Visualization Intellectually (SAVI) learning model in grade V SD Negeri Setono No.95 Surakarta academic year 2017/2018. This research is a classroom action research  and conducted in three cycles and each cycle of two meetings. Each cycle consists of four stages of planning, implementation, observation, and reflection. Data collection techniques using observation, interviews, documentation, and tests. Technique of data validity test using technique triangulation and content validity. Data analysis technique using interactive analysis model and comparative descriptive. The average grade of the class before the action was 43.3 with a percentage of mastery of 2.7% or 1 of 36 students that reaching the minimal mastery criteria that is 72. Finally in cycle III the grade point average increased to 83.87 or 31 of 36 students reached the minimal mastery criteria. Thus it can be concluded that the application of Somatic Auditory Visualization Intellectually (SAVI) learning model can improve understanding of the concept of struggle to maintain independence.